A giant parapharyngeal space carcinoma ex-pleomorphic adenoma: A case report - Salman, Amiruddin; Nor Kamaruzaman, Esa; Mohd Sayuti, Razali (2019)
Parapharyngeal space tumor has been known to be uncommon. It accounts only about 0.5% of head and neck neoplasm. Most of the lesions are benign in nature and salivary gland neoplasm being the most common. A 32-year old Malay gentleman presented with long-standing parapharyngeal mass which medialized the lateral pharyngeal wall. Biopsy was taken intraorally by soft palate mucosal incision revealed carcinoma ex-pleomorphic adenoma and transcervical approach successfully removed the mass in total. Post-operative radiotherapy was commenced and patient is well until recent follow up. Despite of the rarity of pleomorphic adenoma in parapharyngeal space, it should be among the differential diagnosis and a complete removal should be the aim as malignant transformation is possible in this type of pathology. Computed tomography scan extending from base of skull till upper thorax are important in planning the approach for complete removal of the mass followed by radiotherapy in malignant transformation cases.